Speaking elementary - Nolasco, Rob.; Maley, Alan. (Oxford : New York : Oxford University Press, 1987)
A handbook for language teachers who would like to develop their own reading materials or enrich a reading course.
Keywords: English language -- Study and teaching -- Foreign speakers; Reading comprehension